Correlation of sinonasal polyposis with chronic suppurative otitis media - Majeed, Farkhanda; Anjum, Areena; Khan, Yasir A.; Farheen Majid (International Journal of Research in Medical Sciences, 2023)
Background: Aim of the study was to assess correlation of sinonasal polyposis with CSOM. To see the role of lignocaine nebulisation and to compare its role with use of steroids and bronchodilators alone in post bronchoscopy patients. Methods: In the present study, 50 patients of sinonasalpolyposis were subjected to otoscopic, microscopic examination of tympanic membrane findings and tuning fork tests were performed. Pure tone audiometry (PTA) was also done in all patients. High resolution computed tomography (HRCT) of temporal bones and computed tomography (CT) of paranasal sinuses were used to assess otological and sinonasal pathology. Results: Out of 50 patients, males were 26 and females were 24. Age group 11-20 years had 8 males and 8 females, 21-30 years had 5 males and 7 females, 31-40 years had 11 males and 8 females and 41-50 years had 2 males and 1 female. Left side was involved in 6, right in 9 and both sides in 10 patients. Swab cultures revealed pure aerobic isolates in 16, mixed aerobic and anaerobic isolates in 10. Micro-organisms were staphylococcus aureus in 10, Pseudomonas aeruginosa in 6, Streptococcus spp. in 5, Peptostreptococcus in 3 and Bacteroides in 2 cases. The difference was significant (p<0.05). Out of 50 Sinonasal polyp patients, 26 (52%) had CSOM. Type identified was tubotympanic in 12 and atticoantral in 14. There was positive pearsoncorrelation of CSOM with sinonasal polyp (r value of 0.92, p value 0.021). Conclusions: In the present study there was positive correlation of sinonasal polyposis with CSOM. The prevalence rate was 26%. Micro-organisms were Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus spp., Peptostreptococcus and Bacteroides.